Polymer Nanoparticle-Based Chemotherapy for Spinal Malignancies. (9th November 2016) - Ma, Hongyun; Jiang, Weiqian; Ding, Jianxun; Li, Mingqiang; Cheng, Yilong; Sun, Shuo; Fu, Changfeng; Liu, Yi
Abstract : Malignant spinal tumors, categorized into primary and metastatic ones, are one of the most serious diseases due to their high morbidity and mortality rates. Common primary spinal tumors include chordoma, chondrosarcoma, osteosarcoma, Ewing's sarcoma, and multiple myeloma. Spinal malignancies are not only locally invasive and destructive to adjacent structures, such as bone, neural, and vascular structures, but also disruptive to distant organs (e.g., lung). Current treatments for spinal malignancies, including wide resection, radiotherapy, and chemotherapy, have made significant progress like improving patients' quality of life. Among them, chemotherapy plays an important role, but its potential for clinical application is limited by severe side effects and drug resistance. To ameliorate the current situation, various polymer nanoparticles have been developed as promising excipients to facilitate the effective treatment of spinal malignancies by utilizing their potent advantages, for example, targeting, stimuli response, and synergetic effect. This review overviews the development of polymer nanoparticles for antineoplastic delivery in the treatment of spinal malignancies and discusses future prospects of polymer nanoparticle-based treatment methods.